Studies on Cyclobutadiene-Metal Complexes - Efraty, Avishai (My University, 1967)
Reaction of tetraphenylcyclobutadienepalladium halides, [(Ph4C4)PdX2]2, with [(C5H5)M(CO)3]2 (M=Mo or W) gave complexes of the type (Ph4C4)(C5H5)M(CO)X (M=Mo, X=Cl, Br or M=W, X=Br). Conversely, reaction of [(R4C4)PdBr2]2 (R=C6H5, p-CH3C6H4) with [(C5H5)Fe(CO)2]2 or (C5H5)Fe(Co)2Br led not to the expected transfer of the cyclobutadiene ring group onto iron, but to complexes of the type [(R4C4)M(C5H5)]+ FeBr4- (M=Pd or Ni). These were converted into the diamagnetic bromides. [(R4C4)M(C5H5)]+ Br- which, on treatment with sodium methoxide, gave the cyclobutenyl complexes (R4C4OMe)M(C5H5) of palladium and nickel.
The complexes (R4C4)Co(Co)2X (R=C6H5, p-CH3C6H4, X=halogen) have been prepared by ligand-transfer reactions from [(R4C4)PdX2]2. The reactions of (R4C4)Co(CO)2X show considerable similarity to those of (C5H5)Fe(CO)2X, and evidence for a very strong metal-ring bond in the cobalt complex is presented. Reaction of (R4C4)Co(CO)2Br with C6F5Li gave the very stable (R4C4Co(CO)2C6F5. With aromatic hydrocarbons in the presence of AlCl3, (R4C4)Co(CO)2Br gave the stable [(R4C4)Co(π-Arene)]+; cycloheptatriene also reacted with (R4C4)Co(CO)2Br in the absence or a catalyst to give [(R4C4)Co(C7H8)]+. Nucleophilic attack occurred readily at the C7H8 ring in [(R4C4)Co(C7H8)]+ and less readily at the benzene ring in [(R4C4)Co(C6H6)]+ to give (R4C4)Co(cycloheptadienyl) and the (R4C4)Co(cyclohexadienyl) complexes, respectively.
The order of susceptibility of π-complexed ligands in metal d^8 complexes towards nucleophilic attack, cycloheptatriene> benzene> (R4C4)> cyclopentadienyl, is proposed. A novel method for effecting hydride abstraction is reported. Aniline in [(Ph4C4)Co(π-Aniline)]+ is less basic than aniline itself by approximately 1.5 pK units.
Keywords: halides, cyclobutadiene-metal, complexes, reaction, basic